2018
DOI: 10.1002/qj.3379
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reliability of ensemble forecasting systems under serial dependence

Abstract: The problem of testing the reliability of ensemble forecasting systems is revisited. A popular tool to assess the reliability of ensemble forecasting systems (for scalar verifications) is the rank histogram; this histogram is expected to be more or less flat, since, for a reliable ensemble, the ranks are uniformly distributed among their possible outcomes. Quantitative tests for flatness (e.g. Pearson's goodness‐of‐fit test) have been suggested; without exception, however, these tests assume the ranks to be a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
(22 reference statements)
1
14
0
Order By: Relevance
“…This can be harnessed to at least constrain the correlation structure of the ranks to some extent. The result of the presented analysis is a generalized χ 2 ‐test for the (joint) flatness of stratified rank histograms and thus for the reliability of ensemble forecasts, extending the results in Bröcker ().…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…This can be harnessed to at least constrain the correlation structure of the ranks to some extent. The result of the presented analysis is a generalized χ 2 ‐test for the (joint) flatness of stratified rank histograms and thus for the reliability of ensemble forecasts, extending the results in Bröcker ().…”
Section: Introductionsupporting
confidence: 67%
“…We start with fixing some general notation. The general set‐up will be very similar to the one in Bröcker (). The verifications are modelled as a sequence { Y ( n ), n =1,…, N } of random variables with values in the real numbers, with the index n representing the time.…”
Section: Set‐up Notation and The Definition Of Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In order to take into account this multiple testing, the false discovery rate is controlled by the Benjamini–Hochberg procedure (Benjamini & Hochberg, 1995; Benjamini & Yekutieli, 2001) with a control parameter of 0.01, denoted by q in Benjamini and Hochberg (1995). Bröcker (2018) showed that when the observation ranks are serially dependent, the JP tests should be adapted to take into account this temporal dependency. In this study, the lag‐1 autocorrelation of the rank has a median of 0.2 over all the studied locations and lead times and is lower than 0.4 for most of the forecasting systems (raw, post‐processed and aggregated alike).…”
Section: Theoretical Framework and Performance Assessment Toolsmentioning
confidence: 99%